Investigating the Links between Physical Activity, Emotion Regulation, and Mental Health: Comparison in Active, Recreational, and Non-athletes - Nikolija Rakočević; Stanislava Popov; Dragana Brdarić Leka (Primenjena Psihologija)
This research aimed to investigate the relationship between physical activity and mental health, focusing on the potential mediating role of emotional regulation. We investigated whether physical activity predicts the degree of distress and whether this potentially significant relationship can be mediated by two strategies of emotion regulation - cognitive reappraisal and emotional suppression. Then, we tested the mentioned mediation model within three subsamples − active athletes, recreational athletes, and non-athletes. A mediation analysis conducted on the entire sample revealed the existence of partial mediation. In addition to the significant total effect, physical activity had a significant direct effect on distress and a significant indirect effect through both tested emotion regulation strategies. More physical activity predicts more use of cognitive reappraisal, which then predicts lower distress. Also, more physical activity predicts more use of emotional suppression, which predicts higher distress. Such results suggest that engaging in physical activity can lead to a decrease and an increase in distress, depending on which emotion regulation strategy a person relies on. Mediation analyses conducted on subsamples provided arguable confirmation of the mediation model only in the case of recreational athletes. The results obtained within the subsamples are discussed in detail.